2D amorphous bi-metallic NiFe nitrides for a high-efficiency oxygen evolution reaction. Issue 97 (23rd November 2021) - Xu, Yifan; Cheng, Zhenfeng; Jiang, Jingyun; Du, Jiang; Xu, Qun
Abstract : 2D amorphous NiFe–N are synthesized in the designed ternary deep eutectic solvents and achieve superior oxygen evolution performance in alkaline media. Abstract : Two-dimensional bi-metallic NiFe nitrides (2D NiFe–N) are successfully synthesized in the designed ternary deep eutectic solvents under the guidance of DFT calculations. Taking advantage of the unique properties of large-size, ultrathin amorphous 2D structure and modulable electronic structure, the NiFe0.05 –N exhibits extraordinary OER performance with relatively low overpotential of 238 mV at 10 mA cm −2 and durable stability.